2011
DOI: 10.1016/s1349-0079(11)80008-3
|View full text |Cite
|
Sign up to set email alerts
|

The Amelogenin Proteins and Enamel Development in Humans and Mice

Abstract: Before a tooth erupts into the oral cavity, the mineralized enamel and dentin layers begin to develop. During these early stages of enamel formation, an abundant group of proteins known as amelogenins are secreted by ameloblast cells within the developing tooth. These proteins are required for the enamel layer to reach its normal thickness and attain its intricate structure. Human patients with amelogenin gene mutations have a condition referred to as amelogenesis imperfecta, and we have analyzed human gene de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…Enamel is epithelial-derived and formed by ameloblasts during tooth development, which is a complex process regulated by epithelial-mesenchymal interactions [Hu et al, 2007;Simmer et al, 2010]. Defects in amelogenesis are correlated with a specific stage of enamel formation leading to a highly variable phenotype [Simmer et al, 2010;Gibson, 2011]. The different phenotypes have been used over the last decades as classification systems, and various schemes have been proposed [see Aldred et al, 2003;Crawford et al, 2007, for overview].…”
mentioning
confidence: 99%
“…Enamel is epithelial-derived and formed by ameloblasts during tooth development, which is a complex process regulated by epithelial-mesenchymal interactions [Hu et al, 2007;Simmer et al, 2010]. Defects in amelogenesis are correlated with a specific stage of enamel formation leading to a highly variable phenotype [Simmer et al, 2010;Gibson, 2011]. The different phenotypes have been used over the last decades as classification systems, and various schemes have been proposed [see Aldred et al, 2003;Crawford et al, 2007, for overview].…”
mentioning
confidence: 99%
“…This research is supported by studies of amelogenin, which plays a crucial role in enamel development, and is specifically responsible for enamel thickness (Gibson, 2011). Amelogenin genes are present on both the X (AMELX) and Y (AMELY) chromosomes.…”
Section: Discussionmentioning
confidence: 69%
“…Alterations in these genes have shown that differences in their transcriptional products influence proportion of enamel produced (Gibson, 2011; Hu et al, 2012; Cho et al, 2014; Kim et al, 2017; Duan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This research is supported by studies of amelogenin, which plays a crucial role in enamel development, and is specifically responsible for enamel thickness (Gibson, 2011). Amelogenin genes are present on both the X (AMELX) and Y (AMELY) chromosomes.…”
Section: Discussionmentioning
confidence: 69%